Membrane distillation for concentration of protein-rich waste water from meat processing. (December 2021) - Muster-Slawitsch, B.; Dow, N.; Desai, D.; Pinches, D.; Brunner, C.; Duke, M.
Abstract: This work studies a promising waste valorization approach involving recovery of fresh water from protein-rich waste water from the meat processing and rendering industry via membrane distillation (MD). Blood stick water samples from an industrial plant have been treated in batch and continuous tests with two different PTFE membranes (native hydrophobic and hydrophilic coated). Treated water coming from MD permeate was evaluated using various parameters including sodium (for salinity), total organic carbon (TOC) and total nitrogen (TN). Overall, MD was shown to yield concentrated high strength stick water up to a concentration factor of 20 for potential re-use and recover clean water rejecting >99% salinity and TOC, and >95% of TN. Compared to conventional native hydrophobic PTFE, the hydrophilic coated membrane showed higher constant rejection in continuous experiments, but performed with less total flux. Uniquely for the first time in MD studies, the transfer of volatile fatty acids through the membrane into the permeate was explored, showing concentrations of 30–160 mg/L in the permeate appearing more related to hydrophobic surface diffusion than volatile diffusion. While MD for valorization of meat industry wastewater appears viable with correct conditions and membranes, the value of recovered water due to fatty acid presence and other practical considerations, such as membrane cleaning, need to be considered. Graphical abstract: Unlabelled Image Highlights: Meat rendering waste water is challenging to treat but contains valuable resources such as proteins and fats. Wastewater from blood processing was proposed to be concentrated by membrane distillation. Various temperature and flow conditions were tested, as well as hydrophobic PTFE and hydrophilic coated PTFE membranes. Hydrophilic coated PTFE membranes showed lower flux but avoided wetting. Volatile fatty acids permeated via hydrophobic diffusion through the membrane instead of via their volatility.